Heuristic Algorithm for Forming the Service Schedule for the Multistage Systems with a Generalized Resource Criterion - A. Oleinikova, S.; Ya. Kravets, O.; D. Sekerin, V.; E. Gorokhova, A.; I. Gayduk, V. (International Journal of Engineering and Technology, 2018)
The paper suggests one of the approaches to solving the problem of planning multi-stage service systems, the distinguishing feature of which is the availability of time constraints and a resource criterion. At the heart of the approach lie heuristics, which make it possible to obtain a suboptimal solution in an acceptable time. Based on these heuristics, the process of making decisions about assigning jobs to a given time interval, determining the optimal time interval for the return, and estimating the remaining service time are carried out. Â Â Â